(untitled) (Balthazar, 2020)
The following essay concentrates on our bilateral relationship with technology. It puts forward a completely new thesis, that intends to investigate and connect the increasingly intense utilisation of digital devices (specially, smartphones) and our solipsistic attitude. Furthermore, how does the power of technological media influence our values? In order answer this question, the study proposes, as an explanatory criterion, the imitation dynamic. The relationship between us and our devices has been turning into a type of enslavement, in which we are resembling obedient disciples who spend more and more time with the eyes anchored to our screens. The current individualist ethos could reveal itself, partly, as one of the imitative modes which we draw from digital technology.